The Importance of the Role of the Logo in Building Branding on MSMEs - Sutrisno Sutrisno (Universitas Kristen Indonesia Toraja, 2022)
When launching an MSME, MSME branding is very important. MSMEs can increase sales and attract customers with their own brand. By creating websites for MSMEs, creating social media platforms, and providing meaningful logos, MSME branding allows MSMEs to be recognized by the general public. The goal is for sellers to have their own brand, and with the logo of the products being sold, they can also be recognized by the general public. As a result, the logo is extremely important in SMEs. In order for the Istana Gorengan MSME to maximize sales and introduce its products, it is required to produce content for MSMEs, create MSME social media, create MSME websites, and create a new logo for MSMEs. Keywords: , , .